Seeing Through the FOG: A Classroom Exercise Illustrating the Challenges of Sharing Information as Facts, Opinions, and Guesses in Teams. (December 2022) - Romney, Alexander C.; Soderberg, Andrew T.; Okhuysen, Gerardo A.
Information sharing is a critical aspect of effective team functioning. However, it can be challenging to discern whether the information communicated is fact, opinion, or someone's best guess (FOG) due to the varied understandings, assumptions, and interests team members bring to any collaboration. In this article, we introduce a role-play exercise that helps participants better understand the complexities associated with information sharing in teams and how to sort through the FOG associated with information exchanges. Drawing upon research on motivated information processing, this exercise simulates the challenges of information sharing and assists teachers in demonstrating strategies to overcome them.